Analisis Praktik Penyaluran Zakat Fitrah Di Desa Trimulya Ditinjau Dari Perspektif Hukum Islam - Acok Pujiono; Haeran Haeran; Zeni Sunarti; Daud Daud; Kuswanto Kuswanto; Erwina Kartika Devi; Ahmad Hidayat (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to examine the actual mechanisms of zakat fitrah distribution in Trimulya Village and to analyze the practice's conformity with Islamic law and prevailing positive law in Indonesia. A descriptive qualitative method with a normative-empirical legal approach was employed. Primary data were gathered through field observations and in-depth interviews with informants selected via purposive sampling—including the village midwife, religious leaders, official zakat administrators, village officials, and community members acting as zakat payers. Secondary data were obtained through literature reviews, documentary research, and an analysis of relevant legislation. Data analysis utilized the Miles and Huberman interactive model, comprising three stages: data reduction, data display, and conclusion drawing/verification. The study yielded two key findings: First, the mechanism of distributing zakat fitrah to the village midwife in Trimulya is driven by strong emotional ties rooted in local tradition and a community sense of indebtedness; zakat is handed directly to the midwife's residence, after which she redistributes it to her own internal family network. Second, from the perspective of Islamic law, this practice is categorized as an invalid normative deviation. The village midwife is financially capable; thus, she is legally prohibited from receiving zakat and falls outside the eight categories of zakat recipients—a classification that is absolute and defined in Surah At-Taubah, verse 60. Because the requirement regarding the correct recipient was not met, the status of the zakat assets shifted to that of a hibah, meaning the muzaki have not yet fulfilled their Sharia obligation to pay zakat fitrah.